Upaya untuk mengurangi preparasi gigi: Fung shell bridge - Eri H. Jubhari (Journal of Dentomaxillofacial Science, 2007)
Natural tooth can be replaced with many ways, for example with bridge. This kind ofdenture is conventional because too much sound teeth tissue are grinded. Therefore,many designs which grinds as minimal as possible have been tried such as Maryland andRochette designs. As technology develops, Fung Shell System was found. It consists ofone unit bridge called pontic which has a form of porcelain fused to metal and postbridge. Fung bridge is easier and faster to make than conventional bridge. This article isexpected to enrich our knowledge of fung bridge which is as modification of bridge.